2009
DOI: 10.1002/hyp.7502
|View full text |Cite
|
Sign up to set email alerts
|

Spatial–temporal variability and hydrologic connectivity of runoff generation areas in a North Alabama pasture—implications for phosphorus transport

Abstract: Abstract:This study delineated spatially and temporally variable runoff generation areas in the Sand Mountain region pasture of North Alabama under natural rainfall conditions, and demonstrated that hydrologic connectivity is important for generating hillslope response when infiltration-excess (IE) runoff mechanism dominates. Data from six rainfall events (13Ð7-32Ð3 mm) on an intensively instrumented pasture hillslope (0Ð12 ha) were analysed. Analysis of data from surface runoff sensors, tipping bucket rain ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…Structural connectivity relates to the continuum properties of state variables such as soil characteristics and altitude, whereas functional connectivity is process-based and depicts the capacity of water to move in the system in response to a boundary stimulus [Antoine et al, 2009;Wainwright et al, 2011]. In our case, the state variable is the runoff-generating areas, hereafter referred to as rainfall excess areas, and the functional connectivity depicts the runoff-contributing areas (wet areas) [Sen et al, 2010]. The central question resulting from these definitions is how to predict the connectivity of wet areas, given the connectivity of rainfall excess areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural connectivity relates to the continuum properties of state variables such as soil characteristics and altitude, whereas functional connectivity is process-based and depicts the capacity of water to move in the system in response to a boundary stimulus [Antoine et al, 2009;Wainwright et al, 2011]. In our case, the state variable is the runoff-generating areas, hereafter referred to as rainfall excess areas, and the functional connectivity depicts the runoff-contributing areas (wet areas) [Sen et al, 2010]. The central question resulting from these definitions is how to predict the connectivity of wet areas, given the connectivity of rainfall excess areas.…”
Section: Introductionmentioning
confidence: 99%
“…Based on runoff experiments performed on steep forest hillslopes, Gomi et al [2008] discussed the relationships among scale effect, connectivity, land-cover, and rainfall. Sen et al [2010] delineated spatially and temporally variable runoffgeneration areas in an instrumented pasture hillslope. That study demonstrated that the connectivity of these areas and runon both have important impacts on the discharge hydrograph.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, researchers have recognized the importance of hillslope hydrology, not just for watershed-scale hydrologie studies, but also for its applicability in environment;ü, water quality, hydroecology, and hydrogeomorphology studies (e.g., Hewlett and Hibbert 1963;Whipkey 1965;Kirkby 1978Kirkby , 1988O'Loughlin 1990;Bronstert and Plate 1997;Loague et al 2006;Kampfand Burges 2007). A number of hydrologie studies on experimental hillslopes have been conducted under different climatologie, hydrologie, and pédologie conditions and have been used for developing and testing hillslope hydrologie models (Horton 1933;Dunne and Black 1970;Freeze 1978;Kirkby 1988;Bronstert and Plate 1997;Bronstert 1999;Beven 2000Beven , 2002aSrinivasan et al 2001Srinivasan et al , 2002Singh and Woolhiser 2002;Sen et al 2008, 2010: Tromp-van Meerveld and Weiler 2008.…”
mentioning
confidence: 99%
“…Meng et al (2006Meng et al ( , 2008 developed a physicaUy based, distributed rainfall-runoff model called Hortonian Infiltration and Runofi/On (HIRO2).The model, based on an advanced flow-path algorithm, simulates infiltration and ponding times and routes infiltration excess runoff and channel flow at the pixel level (here the smallest unit is 0.5 x 0.5 m [1.64 X 1.64 ft]). One ofthe important features ofthe model is the simulation of runon process (infiltration of upslope runoff at a downslope location or inflow from neighboring pixels) (Martina and Entekhabi 2006), which was found to be present at the study hillslope (Sen et al 2010). Another important feature ofthe model is the simulation of spatial hydrologie connectivity of the runofT generation areas, a significant hydrologie process McDonell 2006a, 2006b;Hopp and McDonell 2009;Michaelides and Chappell 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation